A 6-month study on the pattern of emergency department presentations for schizophrenia and other psychotic disorders during COVID-19 lockdown. (September 2021) - Jagadheesan, Karuppiah; Danivas, Vijay; Itrat, Quratulain; Shekaran, Lokesh; Lakra, Vinay
Highlights: In the six months of the lockdown period, there was an increase in 6.8% psychotic disorders, and this increase was particularly noted for schizophrenia and acute transient psychosis. In the lockdown period, psychotic disorder group included more patients between 26 and 55 years, men, emergency triage category, and hospital admissions. The duration of ED stay was longer for psychotic disorders in the lockdown. Patients with psychotic disorders had increased hospital admissions than patients with mood disorders but the rate of hospital admission in the lockdown was lower than the previous year. Abstract: This study investigated the characteristics of patients with schizophrenia and other psychotic disorders presenting to emergency departments (ED) for psychiatric treatment during the first six months of the COVID-19 lockdown in Melbourne. This cross-sectional data-base study included adult patients in the North West Area Mental Health Service's catchment area who had visited two emergency departments (EDs) during the study period (March 16-September 16, 2020) and the control period (March 16-September 16, 2019). Compared to the control period ( n  = 467), the lockdown period ( n  = 451) had a 6.8% more psychotic disorders. This increase was particularly noted for schizophrenia and acute transient psychosis. In a sub-analysis of psychotic disorder group alone, compared to the control period, more patients were discharged to the community in the lockdown period. In another sub-analysis, compared to the mood disorder group, psychotic disorder group included more patients in 26–35 and 46–55 age groups, men, emergency triage category, and hospital admissions and higher mean duration of ED stay in the lockdown period. Overall, patients with psychotic disorders had increased ED presentations and appeared to be in an emergency state when they present to ED during the lockdown.